2010
DOI: 10.1016/j.polymer.2010.10.048
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms and mechanics of the toughening of epoxy polymers modified with silica nanoparticles

Abstract: The present paper considers the mechanical and fracture properties of four different epoxy polymers containing 0, 10 and 20 wt% of well-dispersed silica nanoparticles. Firstly, it was found that, for any given epoxy polymer, their Young's modulus steadily increased as the volume fraction, v f, of the silica nanoparticles was increased. Modelling studies showed that the measured moduli of the different silica-nanoparticle filled epoxy-polymers lay between upper-bound values set by the Halpin-Tsai and the Nielse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
295
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(319 citation statements)
references
References 53 publications
16
295
0
Order By: Relevance
“…Mechanisms for the toughening effect of nanosilica were discussed as well, and the model from Kinloch et al 22 was confirmed; see the next two sections in this article. Matrix shear banding was the dominant mechanism, matrix void growth was secondary, and the debonding of silica nanoparticles had only a minor effect.…”
Section: Amine-cured Epoxy Resinssupporting
confidence: 55%
See 3 more Smart Citations
“…Mechanisms for the toughening effect of nanosilica were discussed as well, and the model from Kinloch et al 22 was confirmed; see the next two sections in this article. Matrix shear banding was the dominant mechanism, matrix void growth was secondary, and the debonding of silica nanoparticles had only a minor effect.…”
Section: Amine-cured Epoxy Resinssupporting
confidence: 55%
“…16 They found exactly the same 17% improvement in the modulus at 20 wt % nanosilica like Kinloch et al 22 and a 40% improvement at a 40 wt % loading level. The strength was slightly improved at the 40 wt % level.…”
Section: Amine-cured Epoxy Resinsmentioning
confidence: 63%
See 2 more Smart Citations
“…[43][44][45] The extent of plastic deformation of the epoxy is enhanced so as to dissipate more energy in regions surrounding the crack tip. [43,44] . The particulated region is delimited by the dashed line.…”
Section: A Sinusoidally-architected Helicoidal Biocompositementioning
confidence: 99%